Usefulness of Hospital Management Information System at Teaching Hospital (International Journal of Psychosocial Rehabilitation, 2020)
This study examines the issue that hospitals as healthcare organizations in the field of services have a high complexity of resource systems, services, personnel, and infrastructure. Thus, it requires a complex adaptive system as an integrated system of all activities in order to improve performance and service. The purpose of this study is to obtain empirical evidence of the effect of usability, ease of use, computer self-efficacy, and intention to use, on the actual use of technology. The research design uses a quantitative approach to the type of explanatory causality of research. This type of research is hypothesis testing. Data collection by questionnaire survey. The unit of analysis is individual employees who use hospital management information systems. Time horizon uses cross section. The population and sample are the same as the sampling technique is saturated sampling. Data analysis using Path Analysis with AMOS Program software. The results showed that the use (Perceived Usefulness) had a positive effect on intention (Behavioral Intention to Use); usability (Perceived Usefulness) has a significant positive effect on actual technology use; ease of use (Perceived Ease of Use) significant positive effect on intention (Behavioral Intention to Use); ease of use (Perceived Ease of Use) has a significant positive effect on actual technology use; Computer Self Efficacy has no significant effect on intention (Behavioral Intention to Use); intention (Behavioral Intention to Use) has a positive effect on the actual use of technology (Actual technology use); Computer Self Efficacy has no significant effect on actual technology use. The research findings show that the Behavioral Intention to Use variable is not an intervening variable because the variable cannot mediate the effect of Perceived Usefulness, perceived ease of use, and computer self-efficacy toward actual technology use. These findings indicate that there is a mandatory management for users to use SIMRS applicatively.